PERSEPSI MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA TERHADAP ORANG DENGAN HUMAN IMMUNODEFICIENCY VIRUS / ACQUIRED IMMUNE DEFICIENCY SYNDROME - Dewi, Ni Kadek Putri Silvia Maha; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH, 2021)
ABSTRACT Perception is the process of individuals making observations through sensing of certain objects which are then selected, arranged, and interpreted to create a meaningful picture. A negative perception can affect a person's attitude and acceptance which can lead to stigma and discrimination. The purpose of this study was to determine the perceptions of Udayana University Faculty of Medicine students with HIV / AIDS (PLWHA).  This research uses a quantitative approach using descriptive research design with cross sectional design on 102 respondents selected by non-probability sampling, namely accidental sampling. The univariate results of this study indicate that the majority of FK Unud students are at the level of negative perception that is equal to 52.94%. Then, the variable with a greater proportion has a good perception, namely male gender, public health study program, eighth semester, students who have interacted with PLWHA, students who have participated in organizations related to PLWHA, and students who have good interaction status. It was also found that semester level and interaction intensity had a significant relationship with students' perceptions of PLWHA. Therefore, it is suggested that the Faculty and the Study Program provide a program to increase the knowledge of FK students about HIV / AIDS by integrating it into student events to be able to improve students' perceptions of patients, especially PLWHA. Key Words: Perception, PLWHA, Medical Faculty Students